Benefits and challenges of following a user experience design methodology in information systems consulting in South Africa - van den Heever, Jaco (My University, 2013)
This research report chronicles the adoption of a User Experience Design (UXD) methodology at an information systems consulting firm. The report examines the benefits and challenges of adopting a UXD methodology, experienced by project teams and managers of information systems development projects. This research was approached from within the qualitative research paradigm, employing an interpretivist philosophical orientation. Data were gathered through interviews, and the case study was informed by documentary evidence. The research reveals that in addition to the benefits currently documented in previous studies, UXD also complements traditional business analysis and provides additional value to the information systems development lifecycle (SDLC). The study also found that while most challenges proposed by the existing literature were confirmed, the belief that UXD methodologies are rigid and could constrain innovation was opposed. A lack of buy-in from project sponsors and misperceptions about the field of UXD commonly held by project sponsors and team members, were also identified as typical challenges that a UXD practitioner might face.
MBA thesis
Keywords: Information systems; Design methodology